A non-invasive heart rate and blood pressure monitoring system using piezoelectric and photoplethysmographic sensors. (15th June 2022) - Samartkit, Piyawat; Pullteap, Saroj; Bernal, Olivier
Highlights: PZT & PPG-based system is developed for dynamic non-invasive HR and BP monitoring. A modified PTT technique is applied to demodulate pulse signals into SBP and DBP. An engineering application software contributes to dynamic signal monitoring. PZT & PPG sensors have similar operation and high HR accuracy with MAD of 1.78 bpm. The developed system complies with AAMI-BHS accuracy in BP of "Grade A". Abstract: In this work, a non-invasive heart rate (HR) and blood pressure (BP) monitoring system using a lead zirconate titanate (PZT) piezoelectric and photoplethysmographic (PPG) sensor has, preliminarily, been investigated. A modified pulse transit time (MPTT) is applied to demodulate HR, systolic blood pressure (SBP), and diastolic blood pressure (DBP) from obtained BP waveforms. In addition, an engineering application software written by LabView programming is, also, developed for dynamic signal monitoring and processing of desired parameters. Consequently, HR and BP measurements on 15 volunteers are performed and validated against a reference digital sphygmomanometer. The results show equivalent HR from both sensors with a mean absolute difference (MAD) of 1.78 beats per minute. Meanwhile, MADs of SBP and DBP measurements are 2.62 and 1.36 mmHg, complying with AAMI-BHS accuracy of " Grade A ", respectively. Therefore, PZT and PPG-based monitoring system could lead to development of accurate, non-invasive, and low-cost HR and BP devices.